2021
DOI: 10.1111/gcbb.12880
|View full text |Cite
|
Sign up to set email alerts
|

Limited effect of environmental stress on cannabinoid profiles in high‐cannabidiol hemp (Cannabis sativa L.)

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 31 publications
(48 reference statements)
3
26
0
Order By: Relevance
“…For cannabinoid production, as with grain production, precocious flowering may result in reduced floral biomass yield, while plants that do not flower by the end of the season fail to accumulate high concentrations of cannabinoids ( Stack et al, 2021 ). Additionally, cannabinoid profiles change throughout the maturation of the inflorescence, making initiation of flowering an important factor in timing regulatory compliance testing and harvest ( Toth et al, 2021 ; Zhang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…For cannabinoid production, as with grain production, precocious flowering may result in reduced floral biomass yield, while plants that do not flower by the end of the season fail to accumulate high concentrations of cannabinoids ( Stack et al, 2021 ). Additionally, cannabinoid profiles change throughout the maturation of the inflorescence, making initiation of flowering an important factor in timing regulatory compliance testing and harvest ( Toth et al, 2021 ; Zhang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The same authors also reported a decrease in the THC accumulation as a result of gibberellic acid (GA 3 ) treatment (Mansouri et al, 2009a), whereas ethephon (an ET-releasing plant regulator) treatments increased THC content up to 9 fold in the vegetative stage and CBD showed a dose-dependent response (Mansouri et al, 2016). However, in other hemp varieties, ethephon treatment did not cause significant changes in cannabinoid accumulation or CBD : THC ratios (Toth et al, 2021). In another study, Jalali et al performed treatments with SA and GABA in seed-derived plants of the drug-type "Saghez" variety, reporting changes in both enzyme expression of polyketide synthase (OLS), aromatic prenyltransferase (PT), D9-tetrahydrocannabinolic acid synthase (THCAS) and cannabidiolic acid synthase (CBDAS), as well as THC/CBD accumulation, depending on the elicitor concentration (Jalali et al, 2019).…”
Section: Introductionmentioning
confidence: 88%
“…Therefore, several attempts to use stress as means to manipulate resin accumulation in medical cannabis have been carried out (reviewed in Gorelick and Bernstein, 2017 ). In recent studies, the application of several abiotic (flooding, herbicide treatment, wounding damage, heat, and drought) and biotic ( Golovinomyces spadiceus, or Manduca sexta ) stresses has been evaluated in up to 4 medical cannabis varieties ( Toth et al., 2021 ; Park et al., 2022 ). In their experimental setups, drought stress applied during the early flowering stage was effective to cause changes in the cannabinoids profiles, resulting in a significant accumulation of CBG in inflorescences, but up to 70-80% decrease in THC and CBD accumulation, whereas other treatments did not exert any beneficial effects on the cannabinoid accumulation ( Park et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to Campbell [77], greater water availability increased the THC production; however, other edaphoclimatic factors may have influenced this response. Toth et al (2021) [157] evaluated the effects of different stresses, including excess water (flooding). The authors did not observe any influence on the production of THC, CBD, or CBG in relation to the control treatment [157].…”
Section: Water Availabilitymentioning
confidence: 99%
“…Toth et al (2021) [157] evaluated the effects of different stresses, including excess water (flooding). The authors did not observe any influence on the production of THC, CBD, or CBG in relation to the control treatment [157].…”
Section: Water Availabilitymentioning
confidence: 99%